Language, memory, and cognition in infancy and early childhood - Benson, Janette B. , 1956-; Haith, Marshall M. , 1937- (Academic, 2009)
Suitable for researchers, graduate students, and clinicians interested in cognitive development, language development, and memory, as well as those developmental psychologists interested in various aspects of development, this book describes bilingualism, categorization skills, learning disabilities, reasoning, and speech development